Factors influencing Maybank transactional banking employees’ intention to use MyHR2u Mobile On-the-go / Nur Faizah Abd Halim - Abd Halim, Nur Faizah (Faculty of Business and Management, 2019)
With the advancement of technology, Maybank came out with MyHR2u Mobile On-the-go which enables Maybank employees to access their HR Information System called MyHR2u through mobile phone instead of having to access it using personal computer. Some of the problem statements highlighted in this study are technical problems, lack of knowledge in using the system and insecurity and trust issues. The purpose of this study is to investigate the factors that influence the intention to use MyHR2u Mobile On-the-go among Maybank Transactional Banking employees. Moreover, this study aims to identify the relationship between performance expectancy, effort expectancy, social influence, facilitating condition and intention to use MyHR2u Mobile On-the-go. This study involves two theories which are Theory of Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT). The target population in this study consist of Maybank Transaction Banking employees. Hence, this study focuses on employees in Transactional Banking department. Questionnaire was distributed to Transactional Banking employees using Google Form through E-mail and Whatsapp group. In return, 140 responses were received. Results revealed that performance expectancy and facilitating condition have a significant relationship with intention to use MyHR2u Mobile On-the-go. However, effort expectancy and social influence have no significant relationship with intention to use MyHR2u Mobile On-the-go. Regression analysis also depicts that performance expectancy has the highest influence on intention to use MyHR2u Mobile On-the-go.